OVERVIEW OF IOT BASED AGRICULTUREMONITORING SYSTEM - SYEDA FASIHA FATIMA; PROF. SUMERA ALI; DR. ULHAS SHINDE (International Journal of Innovations in Engineering Research and Technology, 2021)
The Indian agriculture sector is contributing 18% to the GDP. About 50% of Indian workforce has got an employment through agriculture and allied sector. Indian economy is dependent on agriculture sector since many decades and the contribution of the sector always important for the development of India. In ancient days the conventional farming was the only method implemented in India. With development of India in last few decades and availability of the technology at affordable costhas opened up the doors of opportunities for Indian agriculture sector.Internet of things (IoT) technology being simple and with availability of the open source hardware and software is contributing for the smart management of the farming activities. This paper presents the overview of agriculturemonitoring bymeans IoT based systems.